Conjugation of amiodarone to a novel cardiomyocyte cell penetrating peptide for potential targeted delivery to the heart - Yurko, Ray; Islam, Kazi; Weber, Beth; Salama, Guy; Zahid, Maliha (Frontiers in Chemistry, 2023)
Modern medicine has developed a myriad of therapeutic drugs against a wide range of human diseases leading to increased life expectancy and better quality of life for millions of people. Despite the undeniable benefit of medical advancements in pharmaceutical technology, many of the most effective drugs currently in use have serious limitations such as off target side effects resulting in systemic toxicity. New generations of specialized drug constructs will enhance targeted therapeutic efficacy of existing and new drugs leading to safer and more effective treatment options for a variety of human ailments. As one of the most efficient drugs known for the treatment of cardiac arrhythmia, Amiodarone presents the same conundrum of serious systemic side effects associated with long term treatment. In this article we present the synthesis of a next generation prodrug construct of amiodarone for the purpose of advanced targeting of cardiac arrhythmias by delivering the drug to cardiomyocytes using a novel cardiac targeting peptide, a cardiomyocyte-specific cell penetrating peptide. Our in vivo studies in guinea pigs indicate that cardiac targeting peptide-amiodarone conjugate is able to have similar effects on calcium handling as amiodarone at 1/15th the total molar dose of amiodarone. Further studies are warranted in animal models of atrial fibrillation to show efficacy of this conjugate.